Resequencing Study Confirms That Host Defense and Cell Senescence Gene Variants Contribute to the Risk of Idiopathic Pulmonary Fibrosis - Moore, Camille; Blumhagen, Rachel Z; Yang, Ivana V; Walts, Avram; Powers, Julie; Walker, Tarik; Bishop, Makenna; Russell, Pamela; Vestal, Brian; Cardwell, Jonathan; Markin, Cheryl R; Mathai, Susan K; et al. (American journal of respiratory and critical care medicine, 2019)
Rationale: Several common and rare genetic variants have been associated with idiopathic pulmonary fibrosis, a progressive fibrotic condition that is localized to the lung. Objectives: To develop an integrated understanding of the rare and common variants located in multiple loci that have been reported to contribute to the risk of disease. Methods: We performed deep targeted resequencing (3.69 Mb of DNA) in cases (n = 3,624) and control subjects (n = 4,442) across genes and regions previously associated with disease. We tested for associations between disease and 1) individual common variants via logistic regression and 2) groups of rare variants via sequence kernel association tests. Measurements and Main Results: Statistically significant common variant association signals occurred in all 10 of the regions chosen based on genome-wide association studies. The strongest risk variant is the MUC5B promoter variant rs35705950, with an odds ratio of 5.45 (95% confidence interval, 4.91-6.06) for one copy of the risk allele and 18.68 (95% confidence interval, 13.34-26.17) for two copies of the risk allele (P = 9.60 × 10-295). In addition to identifying for the first time that rare variation in FAM13A is associated with disease, we confirmed the role of rare variation in the TERT and RTEL1 gene regions in the risk of IPF, and found that the FAM13A and TERT regions have independent common and rare variant signals. Conclusions: A limited number of common and rare variants contribute to the risk of idiopathic pulmonary fibrosis in each of the resequencing regions, and these genetic variants focus on biological mechanisms of host defense and cell senescence.
Keywords: ATP-Binding Cassette Transporters; logistické modely; Idiopathic Pulmonary Fibrosis; Female; GTPase-Activating Proteins; Genome-Wide Association Study; Telomerase; ženské pohlaví; Logistic Models; Mucin-5B; proteiny aktivující GTPasu; High-Throughput Nucleotide Sequencing; genetic variants; protein C asociovaný s plicním surfaktantem; lidé; telomerasa; ABC transportéry; stárnutí buněk; DNA Helicases; idiopatická plicní fibróza; RNA; genetická predispozice k nemoci; studie případů a kontrol; Pulmonary Surfactant-Associated Protein C; mucin 5B; Genetic Predisposition to Disease; Telomere-Binding Proteins; exoribonukleasy; Genetic Variation; Humans; Male; proteiny vázající telomery; Case-Control Studies; idiopathic pulmonary fibrosis; vysoce účinné nukleotidové sekvenování; Pulmonary Surfactant-Associated Protein A; celogenomová asociační studie; interakce hostitele a patogenu; Sequence Analysis, DNA; protein A asociovaný s plicním surfaktantem; targeted resequencing; rare variants; promotorové oblasti (genetika); mužské pohlaví; sekvenční analýza DNA; Host-Pathogen Interactions; Promoter Regions, Genetic; DNA-helikasy; genetická variace; Cellular Senescence; disease risk alleles; Exoribonucleases